Next‐generation RNA sequencing reveals differential expression of MYCN target genes and suggests the mTOR pathway as a promising therapy target in MYCN‐amplified neuroblastoma. Issue 3 (26th September 2012) - Schramm, Alexander; Köster, Johannes; Marschall, Tobias; Martin, Marcel; Schwermer, Melanie; Fielitz, Kathrin; Büchel, Gabriele; Barann, Matthias; Esser, Daniela; Rosenstiel, Philip; Rahmann, Sven; Eggert, Angelika; et al.
Abstract In many cancer types, MYC proteins are known to be master regulators of the RNA‐producing machinery. Neuroblastoma is a tumor of early childhood characterized by heterogeneous clinical courses. Amplification of the MYCN oncogene is a marker of poor patient outcome in this disease. Here, we investigated the MYCN‐driven transcriptome of 20 primary neuroblastomas with and without MYCN amplification using next‐generation RNA sequencing and compared the results to those from an in vitro cell model for inducible MYCN (SH‐EP MYCN‐ER). Transcriptome sequencing produced 30–90 million mappable reads for each dataset. The most abundant RNA species was mRNA, but snoRNAs, pseudogenes and processed transcripts were also recovered. A total of 223 genes were significantly differentially expressed between MYCN‐amplified and single‐copy tumors. Of those genes associated with MYCN both in vitro and in vivo, 32% of MYCN upregulated and 37% of MYCN downregulated genes were verified either as previously identified MYCN targets or as having MYCN‐binding motifs. Pathway analyses suggested transcriptomal upregulation of mTOR‐related genes by MYCN. MYCN‐driven neuroblastomas in mice displayed activation of the mTOR pathway on the protein level and activation of MYCN in SH‐EP MYCN‐ER cells resulted in high sensitivity toward mTOR inhibition in vitro. We conclude that next‐generation RNA sequencing allows for the identification of MYCN regulated transcripts in neuroblastoma. As our results suggest MYCN involvement in mTOR pathway activation on the transcriptional level, mTOR inhibitors should be further evaluated for the treatment of MYCN‐amplified neuroblastoma.